WAYS OF IMMERSION PROGRAMS IMPLEMENTATION IN TEACHING LEGAL ENGLISH - BALABUKHA, Katheryna (Comparative Legilinguistics, 2013)
In this article the author examines the specific features of immersion approach in second language learning, gives brief information concerning the origin and further development of immersion programs. The article provides the description of closely related methods which are considered to be the theoretical basis for immersion programs. The author discloses the relevant elements and objective advantages of the approach mentioned above. The core features and possible modes of the method under analysis are defined. The article presents the way of applying immersion programs which has been worked out to prepare future lawyers for professional communication in a foreign language and introduced at National University “Odessa Academy of Law”, Ukraine.